Perjumpaan Agama dan Budaya: Melacak Konsep dan Gerakan Radikalisme Islam di Indonesia - Basyir, Kunawi (Faculty of Ushuluddin and Religious Study, Universitas Islam Negeri Raden Intan Lampung, 2017)
Religion is always needed in cultured life to give ethical awareness direction so that its cultural results are more meaningful and ideal. Meanwhile, religion requires a cultural medium for it to exist in life, because religion can only be realized concretely in the wilds of cultural life. Human life is always looking for meaning. The search for meaning is important as is the need for foraging and shelter, because in reality the meaning of life is the longing for the Most Holy, it is the most enduring human need. Looking at the above reality, religion is always syncretic with the existing culture. If they violate existing rules or traditions, it will lead to sectarian religious attitudes and will in turn create new problems in understanding the exclusively proprietary religious doctrine. This exclusive religious understanding has been implicated in various circles of Muslims in Indonesia. Looking at it gives us a picture that the portrait of religious life in Indonesia has been a shift that was originally traditionalist-pluralist but with the development of modernization and the existing culture of the face of Indonesian Islam turned into a modernist -radicalist. Thus we try to re-read the dialogue of religion and culture of the archipelago in relation to the concept and movement of Islamic Radicalism of Indonesia.